Microarray profiling predicts early neurological and immune phenotypic traits in advance of CNS disease during disease progression in Trypanosoma. b. brucei infected CD1 mouse brains - Paul Montague; Barbara Bradley; Jean Rodgers; Peter G. E. Kennedy (Public Library of Science (PLoS), 2021)
Human African trypanosomiasis (HAT), also known as sleeping sickness, is a major cause of mortality and morbidity in sub-Saharan Africa. We hypothesised that recent findings of neurological features and parasite brain infiltration occurring at much earlier stages in HAT than previously thought could be explained by early activation of host genetic programmes controlling CNS disease. Accordingly, a transcriptomal analysis was performed on brain tissue at 0, 7, 14, 21 and 28dpi from the HAT CD1/GVR35 mouse model. Up to 21dpi, most parasites are restricted to the blood and lymphatic system. Thereafter the trypanosomes enter the brain initiating the encephalitic stage. Analysis of ten different time point Comparison pairings, revealed a dynamic transcriptome comprising four message populations. All 7dpi Comparisons had by far more differentially expressed genes compared to all others. Prior to invasion of the parenchyma, by 7dpi, ~2,000 genes were up-regulated, denoted [7dpi↑] in contrast to a down regulated population [7dpi↓] also numbering ~2,000. However, by 14dpi both patterns had returned to around the pre-infected levels. The third, [28dpi↑] featured over three hundred transcripts which had increased modestly up to14dpi, thereafter were significantly up-regulated and peaked at 28dpi. The fourth, a minor population, [7dpi↑-28dpi↑], had similar elevated levels at 7dpi and 28dpi. KEGG and GO enrichment analysis predicted a diverse phenotype by 7dpi with changes to innate and adaptive immunity, a Type I interferon response, neurotransmission, synaptic plasticity, pleiotropic signalling, circadian activity and vascular permeability without disruption of the blood brain barrier. This key observation is consistent with recent rodent model neuroinvasion studies and clinical reports of Stage 1 HAT patients exhibiting CNS symptoms. Together, these findings challenge the strict Stage1/Stage2 phenotypic demarcation in HAT and show that that significant neurological, and immune changes can be detected prior to the onset of CNS disease. Author summary Human African Trypanosomiasis, (sleeping sickness), transmitted by the endemic tsetse fly, remains a public health and economic blight for around 70 million inhabitants of sub-Saharan Africa. After a variable period in the haemo-lymphatic system (Stage 1), the trypanosomes cross the blood brain barrier and enter the CNS initiating the encephalitic (Stage 2) of the disease defined by the host's strong immune response with attendant neuropsychiatric debilitating symptoms including sleeping sickness, the hallmark symptom. If not treated, death invariably follows. Our understanding of the contribution of the host's genetics to these two neuropathogenic events is poorly understood. Using a mouse trypanosomiasis model spanning 28 days, we compared the gene expression profiles of trypanosome infected and control mice brains over several time points. By day 7, the activity of over 4,000 genes were altered and genetic programmes, responsible for the development of the Stage 2 encephalitic symptoms were activated prior to any significant breakdown of the blood brain barrier. These findings challenge this traditional Stage1/Stage 2 phenotypic demarcation and accords with reports of Stage 1 patients presenting with Stage 2 encephalitic symptoms and the diagnosis of asymptomatic patients reflects the complex interaction between host and parasite genetics that impact on disease progression.